Effect of Repeated Anodal HD-tDCS on Executive Functions: Evidence From a Pilot and Single-Blinded fNIRS Study - Lu, Hongliang; Gong, Yue; Huang, Peng; Zhang, Yajuan; Guo, Zhihua; Zhu, Xia; You, Xuqun (Frontiers in Human Neuroscience, 2021)
Executive functions are of vital importance in the active cognition process, which is thought to be associated with the dorsolateral prefrontal cortex (DLPFC). As a valid brain stimulation technology, high-definition transcranial direct current stimulation (HD-tDCS) has been used to optimize cognitive function in healthy adults. Substantial evidence indicates that short-term or single anodal tDCS sessions over the left DLPFC will enhance performance on executive functions. However, the changes in performance and cortical activation on executive functions after modulation by repeated anodal HD-tDCS is as yet unexplored. This study aims to examine changes in executive functions produced by nine HD-tDCS sessions (1.5 mA, over left DLPFC, 20 min per session). Our results demonstrate that behavioral performance on three core components (inhibitory control, working memory, and cognitive flexibility) was improved in the anodal group, and enhancement of cognitive flexibility in the anodal group was significantly better than that in the control group. Additionally, a Stroop effect-related decrease in oxy-Hb concentration in the bilateral DLPFC was observed in the anodal group but not the control group. In conclusion, our study found that repeated anodal HD-tDCS sessions can promote executive functions, and alterations in bilateral DLPFC activation can enhance our understanding of the neuroplastic modifications modulated by HD-tDCS and of across-hemisphere transmission of intervention benefits.